EUROPEAN STANDARDS IMPLEMENTATION PRACTICES IN DEVELOPING A BUSINESS PLAN - Крахмальова, Ніна А.; Хвощенко, Євгеній В. (Journal of Strategic Economic Research, 2023)
The article seeks to explore the importance and relevance of developing a business plan for any type of enterprise activities putting a primary focus on the key objectives a well-designed business plan can address. In particular, it is noted that effective business planning contributes to ensuring sustainability of a business entity, thus attaining its better performance as well as enhancing competition in the market in which a business operates. It is emphasized that having a business plan is critical to any enterprise, especially while launching a new project or area of business, since business plan is viewed as a critical tool in delivering a feasibility study and providing a forecast on business project development. The key priority of the research agenda is studying best practices in business planning according to international and European standards. It is observed that there is a whole range of different methods of writing successful business plans based on government, local, national or international standards. From this perspective, most methods were developed by adapting international business planning principles to national settings. In particular, within the framework of this study, the paper is focused on a business plan methodology in accordance with UNIDO and the European Bank of Reconstruction and Development standards, TACIS programmes as well as the KPMG International Cooperative principles. The study suggests a business plan structure in compliance with the above standards along with providing a brief overview of each of them. Apart from this, it is argued that domestic enterprises often face certain problems in implementing their business plans resulted primarily from considering the one or another aspect of the document, thus ignoring the importance of others. Based on the research findings, it is concluded that when developing business plans Ukrainian enterprises should focus not only on the financial aspects of activity planning but also mind the significance of other sections of the business plan structure, since each of them offers its own important information for the investor (in particular, this refers to the section on risk planning which is often underestimated by domestic companies).